Methylation of The Promoter of Survivin Gene May Affect Immunohistochemical Expression of Survivin Protein in Lung Cancers - Budak, Metin (Cerrahpaşa Medical Journal, 2019)
Objective: In the present study, we aimed to investigate the promoter region of the survivin gene adenoma and squamous type lung cancer. Squamous cell carcinoma and adenocarcinoma are the two major histologic types of nonsmall cell lung cancer. Survivin is one of the most important apoptosis inhibitor proteins. As an inhibitor of programmed cell death, this protein is involved in chromosome separation during mitosis and is responsible for drug and radiation resistance against cancer treatments. Method: We investigated the promoter region of the survivin gene by means of methylation-specific Polymerase Chain Reaction (PCR) and evaluated its impact on survivin protein expression following DNA isolation and bisulphite modification in paraffin-embedded normal and tumor tissues of lung cancer patients with squamous cell carcinoma and adenocarcinoma. Results: We detected methylation in the promoter region of the survivin gene in normal and tumor tissues of 24 cases (27%) out of the 78 patients (adenocarcinoma, n=37; squamous cell carcinoma, n=41) included in our study. Among these cases, decrease in methylation by 20%–50% from normal tissues to tumors was observed. Twenty-one cases consisted of 11 adenomas (32% of adenoma cases) and 10 squamous cell tumors (27% of squamous cases). Conclusion: These differences were statistically significant. In addition, a significant increase in survivin expression was observed immunohistochemically in adenoma and squamous type tumor tissues of lung. Survivin protein expression was found to be inversely related to promoter methylation. In this study, promoter methylation was observed for the survivin gene, which was considered an early potential marker in lung cancers. This data supports that further investigations may study survivin protein and methylation as a candidate marker for lung cancer. Cite this article as: Budak M. Methylation of The Promoter of Survivin Gene May Affect Immunohistochemical Expression of Survivin Protein in Lung Cancers. Cerrahpasa Med J 2019; 43(2): 44-49.